Inusual variante del Síndrome de Guillain-Barré asociado a la infección por hepatitis viral C: Reporte de caso - Pérez-Galdos, Proel (2025)
The Guillain-Barré Syndrome (GBS) is an acute autoimmune inflammatory polyradiculopathy. Common clinical manifestations include bilateral progressive muscle weakness, especially in the distal lower extremities, loss of sensation, and decreased or loss of deep tendon reflexes. Patients with hepatitis C are known to be susceptible to numerousextrahepatic manifestations, only seven cases of GBS associated with hepatitis C virus (HCV) infection have been reported so far. The existence of a purely sensory form of GBS remains controversial, as these cases always demonstrate a degree of motor weakness or abnormalities on motor nerve conduction studies and are difficult to distinguish from acute sensory neuropathy, in the present study. We report the case of an acute demyelinating sensory polyneuropathy, as an unusual variant of GBS associated with HCV infection.